Formulasi Sediaan Masker Gel Ekstrak Etanol dari Daun Kembang Sepatu (Hibiscus Rosa-Sinensis L.) Sebagai Pelembab Kulit: Formulation of Ethanol Extract Gel Mask Preparation from Hibiscus Leaves (Hibiscus Rosa-Sinensis L.) as a Skin Moisturizer - Sari, Secillia May; Tanjung, Siti Aisyah; Gunawan, Muhammad; Safriana, Safriana (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Skin often dries out due to evaporation and loss of moisture due to dry air, hot weather, aging, skin diseases, etc., so that the skin surface becomes scaly and wrinkled. Moisturizers consist of ingredients that can form and change the texture of dry and rough skin and reduce water evaporation from the skin. The purpose of this study was to analyze the formulation of a gel mask preparation of ethanol extract from hibiscus leaves (Hibiscus Rosa-Sinensis L.) as a skin moisturizer. This study was conducted using an experimental method using hibiscus leaves (Hibiscus rosa-sinensis L.) as a test material obtained by maceration using 80% ethanol solvent which had previously been tested for phytochemical screening and characterization of simplicia. The stages of this study include: making hibiscus leaf extract, making gel mask preparations, organoleptic tests, homogeneity tests, stability tests, viscosity tests, pH tests, spreadability tests, drying time tests, irritation tests, preference tests and skin moisturizer effectiveness tests. Phytochemical screening results showed that hibiscus leaves contain alkaloids, flavonoids, tannins, saponins, steroids and glycosides. Preparations with concentrations of 5%, 10%, 15% produced a homogeneous and stable gel mask from the first day to the 4th week, the pH of the preparation ranged from 6.30-6.56, the viscosity test produced 4.116-5.067, the spreadability test 6.2-6.7 cm, the dry time preparation test 20-22 minutes, the irritation test on volunteers showed no irritation and itching, the preference test value produced by the panelists liked the preparation from a concentration of 15% in terms of color, aroma and shape, and the effectiveness test as a skin moisturizer for water content taken from the highest concentration of 15% obtained an average result of 32.97 ± 2.93%, and for a decrease in oil content obtained 36.71 ± 6.89%.